A step forward towards the structural characterization of Na2Ti2O5·H2O nanotubes and their correlation with optical and electric transport properties. Issue 3 (15th February 2020) - Esteves, Martín; Fernández-Werner, Luciana; Pignanelli, Fernando; Romero, Mariano; Chialanza, Mauricio Rodríguez; Faccio, Ricardo; Mombrú, Álvaro W.
Abstract: In this work we present the synthesis, structural, morphological, optical and electrochemical characterization of sodium titanate nanotubes (NaNT) obtained by hydrothermal means. According to our detailed structural study, we found that a Na2 Ti2 O5 ·H2 O layered crystalline phase with [TiO5 ] pyramidal square base coordination, utilized as a building block of the nanotubes, explains satisfactorily the experimental results. This is a very important aspect, since the bibliography does not always provide structural information about titanate nanotubes. With respect to the formation mechanism we highlight the crucial role of the post treatment washing in the final crystalline structure of the nanotubes. Simulated X-rays powder diffraction patterns (XRPD), based on real size nanotubes models, were refined with experimental data. Building blocks for the NaNT model were inferred from computational simulations, by means of Density Functional Theory. The obtained tube's model characteristic dimensions were also consistent with SAXS and TEM analysis. In addition, our SAXS analysis suggested that the presence of humidity in the cavities of titanate nanotubes is progressively lost at the 80–100 °C temperature range, in good agreement with thermogravimetric analysis. Electrochemical impedance spectroscopy analysis for dried samples in the temperature range, studied under cooling conditions, revealed a single ionic transport mechanism, probably associated to the in-between [TiO5 ] layers ion transport. However, a secondary process was observed for non-dried samples, during heating conditions, that could be associated to the ionic transport along the water filled tube's cavity, consistent with SAXS analysis. In summary, this work shows an integral approach, through theory and experiment, in order to understand the effect of the structure on the physical and electronic properties of the system. Highlights: Crystalline phase Na2 Ti2 O5 ·H2 O as building block for sodium titanate nanotube. Morphological and structural characterization of NaNT. Computational simulation of structural, vibrational and electronical properties. Two different sodium transport characterization in NaNT.